Representing successful entrepreneurship in the African business environment: A content analysis of Forbes Africa’s cover stories (October 2011 – December 2019/January 2020) - Sibanda, Alundrah Martina-Ann Dadirai (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.